Nurses' barriers when using research information in clinical decision making - Mohamed, Safaa; Thabet, Mona (International Journal of Advanced Nursing Studies, 2018)
Recently, there has been more emphasis on clinical decision making to be a cooperative process, which encompasses shared and parallel decision making with patients and health care teams. For this, nurses’ clinical decision-making is a complicated process with a possibility to affect the provided quality of care and. Therefore, affect patient condition progress. Thus, it is the critical point to study the nurses' barriers to research to identify the starting point of how do nurses currently view, and apply research based information in their decision. The aim of the study is to evaluate the nurses' barriers when using research information in clinical decision making. A descriptive correlation research design was utilized. The sample was consisted of of 140 nurse participants at Minia University hospitals. One tool was used as Barriers to using research information in clinical decision making. This study revealed that the nurse participants agree on the research barriers such as lack of time, lack of organization support to use and implement insufficient nurse skills to use research, and complex nature of research. Thus it was concluded that nurses appraise the value of research utilization, but there were many factors hinder and become the barrier to them to implement research.